Дипинти и граффити на амфорах римской Ольвии - Крапивина, В.В.; Диатроптов, П.Д. (Материалы по археологии, истории и этнографии Таврии, 2014)
Публикуемые материалы найдены, в основном, при раскопках участка Р-25 в южной части Верхнего города Ольвии. Прежде всего, это узкогорлые светлоглиняные амфоры типов В, С, D, Е, РF по классификации Д.Б. Шелова. Датировки типов следующие: В -вторая треть I - середина II вв., С - конец II в., D - первая половина III в., Е - IV - начало V вв. (или конец IV - начало VI вв.), F - конец III - IV вв. Как полагает С.Ю. Внуков, узкогорлые светлоглиняные амфоры производились в Гераклее Понтийской. Материал располагается в соответствии с типами амфор, а в рамках каждого типа - в алфавитном порядке. The published materials were found mainly during the excavations of the plot P-25 in the southern part of Upper city of Olbia. First of all, these are light-clay amphorae of types B, C, D, E and F according to D. B. Shelov’s classification. Dating of types are the following: B — the second third of the 1st - the mid-2nd centuries; C - the end of the 2nd century; D - the first half of the 3rd c.; E - the 4th - the beginning of the 5th cc. (or the end of the 4th - the beginning of the 6th cc.); F - the end of the 3rd - the 4th cc. S. Yu. Vnukov believes that light-clay amphorae were manufactured in Heracleia Pontos. Material is arranged in accordance with the types of amphorae; within every type they are given in alphabetic order.